Leading sustainable improvement in university teaching and learning : lessons from the sector. - Devlin, Marcia; Smeal, Georgia; Mazzolini, Margaret; Cummings, Rick (Deakin University, 2012)
Numerous change forces are currently impacting on Australian higher education leadership through technology, mass education, increased student diversity, sector growth, increased competition, changes to funding, changes in expectations and an increased focus on standards. This research was undertaken to determine what works in terms of university leadership of teaching and learning in such a context. Drawing on the reflections, experience, knowledge and learning of leaders and staff in 22 Australian universities, as well as relevant literature, the research has determined seven insights on such leadership. These insights relate to: institutional strategic alignment; symbolic and fiscal support; workload management; the reduction of tensions; research and scholarship; coordinated support structures; and mechanisms to recognise and reward excellence.